2019
DOI: 10.1089/scd.2018.0234
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensitive Ion Channels Are Expressed in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are potential sources for cardiac regeneration and drug development. hiPSC-CMs express all the cardiac ion channels and the unique cardiac Ca 2+ -signaling phenotype. In this study, we tested for expression of acid sensing ion channels (ASICs) in spontaneously beating cardiomyocytes derived from three different hiPSC lines (IMR-90, iPSC-K3, and Ukki011-A). Rapid application of solutions buffered at pH 6.7, 6.0, or 5.0 triggered rapidly acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…Although ASICs, and in particular ASIC1a, are generally associated with the central and peripheral nervous systems, 58 our expression analyses revealed that ASIC1 is present in both rodent and human cardiomyocytes and is not differentially regulated at the transcriptional level as a result of cellular ischemia in vitro or in vivo. 35 Our evidence of ASIC1 expression in the heart is supported by recent studies that identified ASIC-like currents in hiPSC-CMs 59 and rat cardiomyocytes. 24 In neurons, ASIC1a activation leads to cell death through several possible mechanisms, including calcium overload, 60 regulation of mitochondrial permeability transition pores, 61 and the initiation of necroptosis through direct interaction with, and activation of, RIPK1 (receptor-interacting protein kinase 1).…”
Section: Discussionsupporting
confidence: 76%
“…Although ASICs, and in particular ASIC1a, are generally associated with the central and peripheral nervous systems, 58 our expression analyses revealed that ASIC1 is present in both rodent and human cardiomyocytes and is not differentially regulated at the transcriptional level as a result of cellular ischemia in vitro or in vivo. 35 Our evidence of ASIC1 expression in the heart is supported by recent studies that identified ASIC-like currents in hiPSC-CMs 59 and rat cardiomyocytes. 24 In neurons, ASIC1a activation leads to cell death through several possible mechanisms, including calcium overload, 60 regulation of mitochondrial permeability transition pores, 61 and the initiation of necroptosis through direct interaction with, and activation of, RIPK1 (receptor-interacting protein kinase 1).…”
Section: Discussionsupporting
confidence: 76%
“…Although ASICs, and in particular ASIC1a, are generally associated with the central and peripheral nervous systems 53 , our expression analyses revealed that ASIC1 is present in both rodent and human cardiomyocytes, and is not differentially regulated at the transcriptional level as a result of cellular ischemia in vitro or in vivo 33 . Our evidence of ASIC1a expression in the heart is supported by recent studies that identified ASIC-like currents in hiPSC-CMs 54 and rat cardiomyocytes 23 . In neurons, there are several possible mechanisms by which ASIC1a activation leads to cell death including calcium overload 55 , regulation of mitochondrial permeability transition (MPT) pores 56 , and the initiation of necroptosis through direct interaction with, and activation of, RIPK1 45 .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, ASIC-like currents were also observed in human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), derived from three different hiPSC lines (IMR-90, iPSC-K3, and Ukki011-A). However, in this same study, ASIC-like currents and their protein subunits were absent in adult rat cardiomyocytes ( Zhang et al, 2019 ). This evidence indicates the functional expression of ASIC channels in both, the developing and adult mammalian myocardium.…”
Section: Asic Channels Expressed In the Myocardiummentioning
confidence: 59%